Lifestyle Ambiguity: The Visuals of Cigarette Advertisements in the Dutch East Indies Era - Riyanto, Bedjo; Alimin, Nurhayatu Nufut; Murni, Endri Sintiana (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
The focuses of this research are the visual style reconstruction of cigarette advertisements published in magazines during the colonial era of the Dutch East Indies and the expressions of lifestyle recorded in them. This study examines the visualization and visual style of cigarette advertisements published in magazines in Indonesia from 1925 to 2000. This study also aims to reconstruct the lifestyle in the visual representation of cigarette advertisements as a reflection of the process of social change in Indonesian society during the colonial to the post-colonial period (1925 - 2000). This research employed descriptive analytical methodology, with the main theory of the social history of Art and David Chaney’s lifestyle theory. The visual style of Oriental Modern Eclecticism captures the Indies’ hybrid lifestyle expression, namely: a pseudo-modernity lifestyle as a result of the integration among the colonized communities which were spread across the Dutch East Indies (1925-1942). The cigarette advertisements of that era presented an imaginary world that depicted the harmonious social interactions of various social layers which is contrary to the social reality of the segregated colonial life.